Selective effects of weight and inertia on maximum lifting - Leontijevic, B.; Pazin, N.; Kukolj, M.; Ugarkovic, D.; Jaric, S. (International Journal of Sports Medicine, 2013)
A novel loading method (loading ranged from 20% to 80% of 1RM) was applied to explore the selective effects of externally added simulated weight (exerted by stretched rubber bands pulling downward), weight+inertia (external weights added), and inertia (covariation of the weights and the rubber bands pulling upward) on maximum bench press throws. 14 skilled participants revealed a load associated decrease in peak velocity that was the least associated with an increase in weight (42%) and the most associated with weight+inertia (66%). However, the peak lifting force increased markedly with an increase in both weight (151%) and weight+inertia (160%), but not with inertia (13%). As a consequence, the peak power output increased most with weight (59%), weight+inertia revealed a maximum at intermediate loads (23%), while inertia was associated with a gradual decrease in the peak power output (42%). The obtained findings could be of importance for our understanding of mechanical properties of human muscular system when acting against different types of external resistance. Regarding the possible application in standard athletic training and rehabilitation procedures, the results speak in favor of applying extended elastic bands which provide higher movement velocity and muscle power output than the usually applied weights.